2007 IEEE International Conference on Automation Science and Engineering 2007
DOI: 10.1109/coase.2007.4341767
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Annealing Algorithm for Daily Nursing Care Scheduling Problem

Abstract: Nursing, with the primary mission to provide quality services to patients, is accompanied by a serial of activities like patients assessment, outcomes identification for patients. In general, there has been less attention on ensuring that nurses provide nursing cares in a timely and accurate fashion. Consequently, in this paper, considering the similarity to the traditional job shop scheduling problems, we will model the daily nursing care scheduling problems and propose an efficient scheduling method based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In the literature study by Ref. 23 16. The need of a nurse for any shift (minimum, maximum or specified number) In this study, the grouping specified in the study of Cheang et al 23 has been taken consideration based on 1, 5, 6, 7, 10, 12, 13, 15, 16 constraint types.…”
Section: Constraints Usedmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature study by Ref. 23 16. The need of a nurse for any shift (minimum, maximum or specified number) In this study, the grouping specified in the study of Cheang et al 23 has been taken consideration based on 1, 5, 6, 7, 10, 12, 13, 15, 16 constraint types.…”
Section: Constraints Usedmentioning
confidence: 99%
“…Dias et al 12 , Chiaramonte and Chiaramonte 14 , Maenhout and Vanhoucke 15 improved new heuristic models for nurse scheduling problem. Cheng et al 16 , Parr and Thompson 17 , used simulated annealing method for nurse scheduling. Maenhout and Vanhoucke 18 and Brucker et al 19 , set new data sets to compare suggested different models.…”
Section: Introductionmentioning
confidence: 99%
“…Some researches proposed to find the optimal solution based on mathematical programming method, linear programming, nonlinear programming, multi-objective programming, dynamic programming, parameter planning, heuristic algorithm, hill-climbing algorithm, simulated annealing algorithm, etc. [13]- [18].…”
Section: Introductionmentioning
confidence: 99%
“…Many of these methods use meta-heuristic approaches, like the Electromagnetic method [10], Scatter Search [9], various Genetic Algorithms [11], [12], [13], [14], Tabu Search [15], Variable Neighbourhood Search (VNS) [16], GRASP [17], Memetic Algorithms [18], and Simulated Annealing [19].…”
Section: Introductionmentioning
confidence: 99%